Pelaksanaan Pembelajaran Matematika bagi Anak Dyscalculia Kelas III di SD Negeri 01 Limau Manis - Khairunisa, Widya; Sopandi, Asep Ahmad (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2019)
The purpose of this study is to describe and determine the learning design, learning implementation, learning evaluation, the obstacles encountered during learning also efforts to overcome these obstacles for children with dyscalculia in Elementary School 01 Limau Manis. In this research, researcher uses descriptive qualitative method. The subject in this study is mathematic teacher. In this study, researcher used observation , interview and documentation as the technique of data collection. Results obtained in this study are the design of learning mathematics which is consists of Lesson plan and syllabus in accordance with the curriculum. The implementation of mathematics learning carried out for seven hours in a week. The implementation of learning includes 3 phases namely introduction, core activity and closing activity. Learning evaluation is done after the lesson ended by a written test form. The preparation of the program teacher did not experiencing problems, but other Teacher's constraints came during the learning, namely classroom management, during the learning process there are students who pay attention and some of them are did not pay attention. Teacher's effort to overcome these obstacles is giving more attention to their students.